Advanced Breast Cancer - Untch, Michael; Fasching, Peter A.; Haidinger, Renate; Harbeck, Nadia; Jackisch, Christian; Lüftner, Diana; Müller, Volkmar; Schumacher-Wulf, Eva; Würstlein, Rachel; Thomssen, Christoph (Geburtshilfe und Frauenheilkunde, 2022)
Over the past few years, there have been many developments in the treatment of advanced breast cancer; these have been incorporated into national and international treatment guidelines, resulting in an improved prognosis for these patients. The 6th International Consensus Conference for Advanced Breast Cancer (ABC6) was held in November 2021. The aim is to standardize the treatment of advanced breast cancer based on a high level of evidence, and to make new treatment options accessible to all patients. In this article we discuss the ABC6 consensus in the context of German treatment guidelines, and compare it with clinical practice in Germany. The authors refer to the current recommendations of the Breast Cancer Working Group for Gynecological Oncology (AGO Mamma) published in March 2022. The AGO Breast Cancer Guidelines are updated annually. Since discrepancies between national and international guidelines can occur due to country-specific regulations, this is a useful comparison to make. The German authors refer to the voting results of the ABC6 panelists from 6 November 2021.In der Behandlung des fortgeschrittenen Mammakarzinoms gab es in den letzten Jahren zahlreiche Fortschritte, die in internationale und nationale Therapieempfehlungen eingeflossen sind und dazu beigetragen haben, die Prognose der Patient*innen zu verbessern. Im November 2021 tagte die 6. „Internationale Konsensuskonferenz zum fortgeschrittenen Mammakarzinom“ (ABC6: 6th International Consensus Conference for Advanced Breast Cancer). Ziel ist es, die Behandlung des fortgeschrittenen Mammakarzinoms weltweit auf hohem Evidenzlevel zu standardisieren und neue Therapieoptionen allen Patient*innen zugänglich zu machen. Im vorliegenden Manuskript geht es darum, den ABC6-Konsensus vor dem Hintergrund der deutschen Therapieempfehlungen zu diskutieren und mit dem klinischen Vorgehen in Deutschland abzugleichen. Die Autoren beziehen sich auf die aktuellen Empfehlungen der Arbeitsgemeinschaft gynäkologische Onkologie, Kommission Mamma (AGO Mamma) vom März 2022. Die Empfehlungen der AGO Mamma werden jährlich aktualisiert. Ein solcher Abgleich erscheint sinnvoll, da aufgrund länderspezifischer Besonderheiten Abweichungen zwischen internationalen und nationalen Empfehlungen bestehen können. Die deutschen Autoren beziehen sich auf die Abstimmungsergebnisse der ABC6-Panelisten vom 06. November 2021.
Keywords: advanced breast cancer; systemic therapy; treatment sequencing; oligometastasis; brain metastases; supportive treatment